Testing Opuntia ficus-indica genotypes for resistance against Dactylopius coccus (Hemiptera: Dactylopiidae) - Berhe, Yemane Kahsay; Portillo, Liberato; Vázquez-Bolaños, Miguel (Revista Colombiana de Entomología, 2023)
Besides being a beneficial insect when it is cultivated for the production of carminic acid, the cochineal insect (Dactylopius coccus) is also a threat to the prickly pear cactus (Opuntia ficus-indica), a plant that is extremely important as a source of food, cattle feed, income, and soil and water conservation. A crucial component of an integrated pest management approach is the use of resistant varieties. In a greenhouse, a test for resistance of four cactus pear genotypes to cochineal insects was conducted at the University of Guadalajara, Center of Sciences for Biology and Agriculture. Three of these genotypes (‘Punto 1’, ‘Punto 2’, and ‘Sandate 2’) were shown to be non-hosts for D. coccus. These genotypes can be used for further research and development purposes of prickly pear cactus.